Aspects of Littorinid Biology 1998
DOI: 10.1007/978-94-011-5336-2_22
|View full text |Cite
|
Sign up to set email alerts
|

Imposex in Nucella lapillus and intersex in Littorina littorea: interspecific comparison of two TBT-induced effects and their geographical uniformity

Abstract: Two different tributyltin (TBT)-induced virilisation phenomena in prosobranch snails -intersex in Littorina littoreaand imposex in Nucella lapillus -are compared in order to facilitate their simultaneous use in geographical large scale effect monitoring surveys. Imposex in dogwhelks is a more sensitive biomarker and should be used in areas that are only slightly or moderately contaminated with TBT (ambient TBT concentrations < 2.0 ng as Sn 1-1). The assessment of intersex intensities in periwinkle populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
2
28
0
2
Order By: Relevance
“…In contrast, recent studies with nonhermaphroditic prosobranch snails demonstrated that exposure to very low ambient concentrations of organotin compounds resulted in a masculinisation and sterilisation and therefore in reproductive failure in the female snails (Oehlmann et al, 1998;Schulte-Oehlmann et al, 1997). The phenomenon of intersex and imposex (pseudohermaphrodism) presented by these highly sensitive species Minchin et al, 1997;, may be a species or even sub-class specific effect.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, recent studies with nonhermaphroditic prosobranch snails demonstrated that exposure to very low ambient concentrations of organotin compounds resulted in a masculinisation and sterilisation and therefore in reproductive failure in the female snails (Oehlmann et al, 1998;Schulte-Oehlmann et al, 1997). The phenomenon of intersex and imposex (pseudohermaphrodism) presented by these highly sensitive species Minchin et al, 1997;, may be a species or even sub-class specific effect.…”
Section: Discussionmentioning
confidence: 88%
“…VDSI is the only index that responds effectively over a broad range of imposex. It is useful in assessing the reproductive capacity of the studied population; populations with a mean VDSI above IV are comprised of sterile females, and show reduced reprodutive capacity (Gibbs & Brian, 1994;Oehlmann et al, 1996Oehlmann et al, , 1998Stroben et al, 1995). VDSI was obtained through two different approaches: (1) by using the scale of Gibbs (Gibbs & Bryan, 1987), and (2) by using a modified scale of seven levels of imposex, developed by Fernandez et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…Two of the best known cases of endocrine disruption in wildlife are (i) the formation of imposex in female prosobranch snails in tributyltin (TBT) polluted areas (Oehlmann et al 1998;Santos et al 2005;Wirzinger et al 2007) and (ii) the demasculinization of male or "super-feminization" of female alligators in Lake Apopka in Florida, USA, associated with a pesticide spill as well as several decades of extensive agricultural activity around the lake and related pesticide and nutrient runoff (Guillette et al 1994).…”
Section: Introductionmentioning
confidence: 99%